2005
DOI: 10.1111/j.1471-4159.2005.03476.x
|View full text |Cite
|
Sign up to set email alerts
|

Opposing effects of phorbol‐12‐myristate‐13‐acetate, an activator of protein kinase C, on the signaling of structurally related human dopamine D1 and D5 receptors

Abstract: The 'cross-talk' between different types of neurotransmitters through second messenger pathways represents a major regulatory mechanism in neuronal function. We investigated the effects of activation of protein kinase C (PKC) on cAMPdependent signaling by structurally related human D1-like dopaminergic receptors. Human embryonic kidney 293 (HEK293) cells expressing D1 or D5 receptors were pretreated with phorbol-12-myristate-13-acetate (PMA), a potent activator of PKC, followed by analysis of dopamine-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 71 publications
1
24
0
Order By: Relevance
“…It should be noted that the effect of Gö6983 on D 1 -stimulated signaling was not observed in a recent study by Jackson et al, where Gö6983 had no effect on D 1 receptor accumulation of cAMP. Surprisingly, PMA treatment potentiated D 1 receptor signaling (Jackson et al, 2005). Such discrepancies may be due to differences in experimental procedures and perhaps more importantly differences in the expression/activation profile of PKC isozymes.…”
Section: Pkc Inhibitors Mimic the Effects Of Etoh On D 1 -Dependent Smentioning
confidence: 93%
“…It should be noted that the effect of Gö6983 on D 1 -stimulated signaling was not observed in a recent study by Jackson et al, where Gö6983 had no effect on D 1 receptor accumulation of cAMP. Surprisingly, PMA treatment potentiated D 1 receptor signaling (Jackson et al, 2005). Such discrepancies may be due to differences in experimental procedures and perhaps more importantly differences in the expression/activation profile of PKC isozymes.…”
Section: Pkc Inhibitors Mimic the Effects Of Etoh On D 1 -Dependent Smentioning
confidence: 93%
“…We have previously reported that in HEK-293 cells heterologously expressing the human D 5 R, stimulation of D 5 R inhibits NADPH oxidase activity, which is PKA-independent, partly PLD dependent, and partly due to interference with the distribution and assembly of NADPH oxidase components (34). Jackson et al have also reported that PMA increases D 1 R but decreases D 5 R signaling (15). Therefore, it is necessary to use cell lines that heterologously and exclusively express D 1 R or D 5 R to distinguish the mechanisms of involved in D 1 R or D 5 R activation because there are no commercially available D 1 -like receptor agonists or antagonists that can distinguish D 1 R from D 5 R. We tested the hypothesis that a specific PKC isoform may be involved in the D 1 R-mediated inhibition of NADPH oxidase activity.…”
Section: Introductionmentioning
confidence: 98%
“…Phorbol-12-myristate-13-acetate (PMA), a direct activator of PKC, stimulates adenylyl cyclase activity and enhances agonist-induced cAMP production (15). In addition, activation of PKC with PMA stimulates intracellular cAMP production in human eosinophils, in the absence of any agonist (17).…”
Section: Introductionmentioning
confidence: 99%
“…The D 5 R may also stimulate phospholipase C PLC/PKC activity (Sahu et al, 2009). In contrast, increasing PKC inhibits constitutive and dopamine-mediated stimulation of cAMP production via D 5 R (Jackson et al, 2005). Thus, D 1 R and D 5 R may increase cAMP by unique intracellular signaling pathways.…”
mentioning
confidence: 99%